Penerapan Model Pembelajaran Project Based Learning terhadap Peningkatan Kemampuan Berpikir Kritis dan Disposisi Matematis Siswa - Ikhbar Hafidzino Paranduri (Universitas Indraprasta PGRI, 2018)
The purpose of this study was to determine the final achievement, improvement of critical thinking skills, and mathematical dispositions through project based learninglearning models. The population in this study were eighth grade students in one of the State Junior High Schools in Serang City 2014/2015 academic year. The sample was chosen by cluster random sampling technique from 8 classes, obtained one experimental class and one control class. The research method used is quasi-experimental method with non-equivalent research design. The number of samples in the experimental class and control class amounted to 30 students. The results showed: Mathematical critical thinking ability of students who obtained a project based learning in the high category. Enhancement students' critical thinking skills who obtain project based learning that are in the medium category. Mathematical disposition of students who obtain a project based learning model that belongs to the medium category. Enhancement mathematical disposition of students who obtain project based learning in the low category.